Zawadzka, E., Filipiak, S. (red.). (2022). Wielowymiarowość funkcji wykonawczych – perspektywa rozwojowa i kliniczna. Wydawnictwo Uniwersytetu Marii Curie-Skłodowskiej, ss. 270 - Tyburski, Ernest (Przegląd Psychologiczny, 2024)
Abstrakt